Exploration of research on Internet of Things enabled smart agriculture. (2023) - Bharath Kumar, T.; Prashar, Deepak
Abstract: Since we have required so much food to be a major economic country in the world, existing or traditional farming methods and storage methods are not adequate to increase production and maintenance for future purposes. The Internet of Things in Agriculture leads to creativity in areas such as Crop Maintenance and Tracking, Animal Farming, Fishing, Millet Crops, and so on. This paper investigates the different technologies, protocols, sensors used in recent research in sustainable farming.